Authority, Power, Influence and Social Control: A Theoretical Synthesis - Grimes, A. J. (Academy of Management Review, 1978)
Authority and power are usually not conceptually distinct, but for clarification, they are considered extremes on a control continuum. Power is conceptualized as influence and social control, the former reducing and latter reinforcing authority. These constructs permit reexamination of authority and leadership.